Group Classification of the General Evolution Equation: Local and Quasilocal Symmetries - Zhdanov, R.; Lahno, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
We give a review of our recent results on group classification of the most general nonlinear evolution equation in one spatial variable. The method applied relies heavily on the results of our paper, Acta Appl. Math., 69, 2001, in which we obtain the complete solution of the group classification problem for a general quasilinear evolution equation.